Evaluating the Impact of Installed Capacity and Actual Production Volume on the Operational Efficiency of Regional Water Supply Company - Darno, Darno; MD Arifin, Khadijah binti; Purnamasari, Wulan; Fittriya, Nurul Laili (Jurnal Logistik Indonesia, 2025)
In evaluating the performance of PDAMs in various regions, the gov-ernment must also look at the problems that occur in a regional drinking water company such as customer water quality, customer growth, prof-itability, liquidity and financial performance solvency. For this reason, local governments need to evaluate performance in order to improve performance in the company. Generally, companies still use the tradi-tional approach in measuring performance that comes from company financial information, along with the times there is performance meas-urement using the balanced scorecard method, this method is a meas-urement method that offers both financial and non-financial measure-ments. This study aims to determine the effect of installed capacity on opera-tional performance to determine the effect of real production volume on operational performance and to find out which is the most influential between installed capacity and real production volume on the opera-tional performance of PDAMs in West Java, Banten and Jakarta in 2018. In this study the author uses a quantitative approach. This research da-ta collection uses secondary data, which is obtained from the report on the results of the 2018 PDAM performance evaluation issued by BPKP and BPPSPAM. This research uses SPSS multiple regression analysis tool. The results show that the Installed Capacity has a minimum value of 188, the maximum value of Installed Capacity is 20,238. The Real Pro-duction Volume has a minimum value of 146, the maximum value of the Real Production Volume of 19,752 that occurs. Operational perfor-mance has a minimum value of 0.81, the maximum value of Opera-tional Performance is 1.69. The mean value of Operational Performance is 1.2547.